IMPLEMENTASI PENDIDIKAN DEMOKRASI MELALUI PEMBELAJARAN PKn UNTUK MEMBENTUK WARGA NEGARA YANG BERTANGGUNG JAWAB (Studi Kasus Eksplanatoris di SMP Islam Fathia Kota Sukabumi) - Septiana, Tina (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2022)
This research is motivated by: (1) The decline in the Civics learning process which causes students to concentrate less in the teaching and learning process. (2). The tendency of educators who teach is limited to imparting knowledge without any change in students' attitudes and behavior. (3). The creativity of Citizenship Education learning models among junior high school teachers is still less active, creative and innovative. (4). There is a demand that democratic education through citizenship education be taught to include the development of civic intelligence, civic participation and civic responsibility. Based on this, researchers conducted research entitled